Hey there! :)
Answer:
(g-f)(10) = 279/10.
Explanation:
Given:
![f(x) = x^(-1)](https://img.qammunity.org/2021/formulas/mathematics/college/nw1blv9qnpt2lfw31blezfxdkq2s03nwij.png)
and
![g(x) = 2x + 8](https://img.qammunity.org/2021/formulas/mathematics/college/5byiu6p5ar2xvpyuh8finv1zum5p2b65cy.png)
Begin by solving for (g-f) by subtracting f(x) from g(x):
![(g-f)(x) = 2x + 8 - x^(-1)](https://img.qammunity.org/2021/formulas/mathematics/college/i6qreve18tetpttmmmsb6ocba07rq0s2wg.png)
Substitute in 10 for x in the equation to solve this problem:
![(g-f)(10) = 2(10) + 8 - 10^(-1)](https://img.qammunity.org/2021/formulas/mathematics/college/re6npy4q20tmpx0faayk6c9mwg03snn9e0.png)
Simplify:
![(g-f)(10) = 20 + 8 - (1)/(10)](https://img.qammunity.org/2021/formulas/mathematics/college/jxaf759qyzgvjdk6d1b7ccn8ax5zu88rop.png)
Create a common denominator to simplify further:
![(g-f)(10) = (200)/(10)+ (80)/(10) - (1)/(10)](https://img.qammunity.org/2021/formulas/mathematics/college/rza5i7lnrhasf8mi44wyuh5vrhiwnhefe4.png)
![(g-f)(10) = (279)/(10)](https://img.qammunity.org/2021/formulas/mathematics/college/l4q4fef50vful180j99fbytyllz794y5rp.png)
Therefore:
(g-f)(10) = 279/10.